Balancing Act: Dual-Role Conflict and Job Stress in Female Healthcare Workers - Relian Tegar Lesmanto; Sutarto Wijono (Pattimura University, 2024)
This study investigates the relationship between dual-role conflict and job stress among married female nurses working at Hospital X in Magelang. The hospital's policy flexibility in the new normal era aims to enhance healthcare quality, but this also leads to job stress among nurses due to heavy workloads. Interviews with ten married nurses revealed various stress-related issues, highlighting the need for further research. The study defines job stress as the body's response to high job demands and dual-role conflict as the interference between job and family roles. A total of 90 female nurses participated in the study, with data collected via questionnaires using Likert scales. Descriptive statistics showed high levels of dual-role conflict and moderate job stress among participants. Validity and reliability tests confirmed the suitability of the measurement tools used. Pearson correlation analysis revealed no significant relationship between dual-role conflict and job stress (r = -0.073, p > 0.05). The findings suggest that while dual-role conflict levels are high, they do not significantly contribute to job stress among the nurses. Factors such as manageable role conflicts and supportive spouses may mitigate the impact. This study aligns with previous research indicating that dual-role conflict does not necessarily increase job stress among working women. Despite limitations, the study underscores the importance of considering various factors influencing job stress and suggests that other elements may play a more critical role in affecting the stress levels of female nurses at Hospital X.